Structurally Accepted Crime: Domestic Violence in Pakistan - Dr Rafia Naz Ali (Journal of Peace, Development and Communication, 2022)
Domestic violence is a major social issue because of its various severe physical, psychological, emotional, and social implications. When a culture rationalises such anti-human practises and gives them a structural form, they become part of the structural framework. Domestic violence is considered a private matter, though it is the most common crime in Pakistan. No one paid heed to such violence unless disfigurement or death took place. Two provinces of Pakistan ratified a law on domestic violence, but there is no national legislation on the issue. Such violence comes under the ambit of the Criminal law, which prescribes a death sentence in the case of femicide and various terms of imprisonment depending on the nature of the wound. Domestic violence is a significant issue in Pakistan. To know the legal reality of a system, analysis of court decisions must be complemented by the research and work of other legal bodies. The study will help to improve the existing laws and lead to the introduction of new laws, social and political policies to solve the problem of domestic violence.